Towards a Privacy Diagnosis Centre : Measuring k-anonymity - Mirakabad, Mohammad Reza Zare; Jantan, Aman; Bressan, Stephane (2008)
Most of the recent efforts addressing the issue of privacy have focused on devising algorithms for the anonymization and diversification of data.